Cost-Analysis of the Different Treatment Modalities in X-Linked Dystonia–Parkinsonism - De Roxas, Ranhel C.; Jamora, Roland Dominic G. (Frontiers in Neurology, 2019)
Background: X-linked dystonia-parkinsonism (XDP) is a debilitating disease endemic in the Philippines. Several oral medications as well as botulinum toxin A (BoNT-A) injection and deep brain stimulation (DBS) surgery appear to be the cornerstone of treatment in XDP, which are commonly used in combination. Being a chronic progressive disease, it is an economic burden to the patient and their families. Thus, we aim to perform a comparative analysis of the associated healthcare costs for the therapeutic options used in XDP. Methodology: A questionnaire assessing the healthcare costs in the management of XDP was designed and administered through an interview with the XDP patients or their caregivers. We analyzed the data and a bootstrap analysis was also done to obtain a more generalizable estimation of the costs. Results: A total of 110 gene-positive XDP patients were included in this study. The mean total annual cost per patient was USD 4,861.23 (USD:PHP 1:50, as of January 8, 2018). More than half of the patients (n=61, 55.5%) received both oral medications and BoNT-A injection while 42 patients (38.2%) received oral medications alone. Only seven patients underwent DBS with a reported estimated cost of USD 50,931.43. The bootstrap analysis confirmed the estimates done in this study. Conclusion: The estimated costs in the management of XDP was shown to be 30 times the average annual health expenditure of an average Filipino. This calls for more government effort to provide comprehensive care for chronic and debilitating diseases such as XDP.